1988
DOI: 10.1007/bf00336889
|View full text |Cite
|
Sign up to set email alerts
|

Lack of homogeneity of receptive fields of visual neurons in the cortical area 18 of the cat

Abstract: The receptive fields of "complex" neurons within area 18 of the cerebral cortex of the cat were determined by a computer-assisted method using a moving light bar substantially shorter than the long diameter of the receptive field as a visual stimulus. The visual cells repeatedly generated nerve impulses when the stimulus crossed well-defined "active points" within their receptive fields. Outside of these active points, the cells remained silent. It is suggested that the receptive fields are formed by a discont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Large receptive fields have long been encountered in the visual cortex (for review, see McIlwain, 1976;Maunsell and Newsome, 1987;Dinse et al, 1991). Their internal structure, like that of AI neurons, may be based on response strength and timing (Bear et al, 1971;Sasaki et al, 1971a,b;Henry, 1977;Palmer and Davis, 1981;Reinis et al, 1988), resulting in gradients that may account for many of the static and dynamic response properties exhibited by visual cortical neurons (Palmer and Davis, 1981;Albrecht and Geisler, 1991;Reid et al, 1991;Tolhurst and Dean, 1991;Jagadeesh et al, 1993). Simple cells in the primary visual cortex of the cat exhibit a latency gradient across the receptive field such that fluctuations in membrane potential evoked by moving stimuli are predicted accurately by the linear summation of the temporal response properties to stationary stimuli (Jagadeesh et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large receptive fields have long been encountered in the visual cortex (for review, see McIlwain, 1976;Maunsell and Newsome, 1987;Dinse et al, 1991). Their internal structure, like that of AI neurons, may be based on response strength and timing (Bear et al, 1971;Sasaki et al, 1971a,b;Henry, 1977;Palmer and Davis, 1981;Reinis et al, 1988), resulting in gradients that may account for many of the static and dynamic response properties exhibited by visual cortical neurons (Palmer and Davis, 1981;Albrecht and Geisler, 1991;Reid et al, 1991;Tolhurst and Dean, 1991;Jagadeesh et al, 1993). Simple cells in the primary visual cortex of the cat exhibit a latency gradient across the receptive field such that fluctuations in membrane potential evoked by moving stimuli are predicted accurately by the linear summation of the temporal response properties to stationary stimuli (Jagadeesh et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Simple cells in the primary visual cortex of the cat exhibit a latency gradient across the receptive field such that fluctuations in membrane potential evoked by moving stimuli are predicted accurately by the linear summation of the temporal response properties to stationary stimuli (Jagadeesh et al, 1993). Reinis et al (1988) reported that visual neurons of cat cortical area 18 fire repeatedly only when the visual stimulus is present at precisely defined locations within the receptive field, and they postulated that a population of such neurons could detect a moving image. If gradients in latency and response strength across AI receptive fields are operating similarly, then we would predict that such a neuron would exhibit sensitivity to a train of transient sounds that produce so-called "apparent sound motion" (Perrott, 1974(Perrott, , 1982.…”
Section: Discussionmentioning
confidence: 99%
“…For any given pair of corresponding retinal locations, different neurones with different tuning characteristics will be stimulated. The strength of this response will be proportional to the strength of the input, the strength of the connection to that eye, the activity of other neurones, and perhaps any inhibitory signals from other (differently tuned) neurones (Reinis et al, 1988). In this way, each stimulus will excite a population of binocular neurones with specific tuning characteristics and this "double" population will be different from the population stimulated during normal nonrivalrous viewing because for many retinal locations, two different sets of features will coincide.…”
Section: No Rivalrymentioning
confidence: 99%